2018
DOI: 10.1111/gec3.12414
|View full text |Cite
|
Sign up to set email alerts
|

Disability studies and development geography: Empirical connections, theoretical resonances, and future directions

Abstract: Scholarship that jointly considers disability and development has advanced over the past decade to include greater attention to the shared histories of colonialism, racism, and the disability category and the relationships among developmental states, ideas about disability, and development projects. A handful of geographers have also directly addressed disability and development or disability in the “developing world” context. This paper reviews current scholarship and highlights three areas where disability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…My research has identified the need for more attention to the materiality of family caregiving of children needing long‐term care in feminist geography literature. Feminist techno‐scientists and posthumanists are questioning human/nonhuman relations and theorizing about mother/child assemblages that recenter discourses away from medical and social models of disability (Goodley et al., 2014; Hamraie, 2015; Haraway, 2013; Jampel and Bebbington, 2018). This work contributes to that discussion by not only presenting Jane and Ichabod as individuals but also as assemblages that function (or not) within wider power assemblages (human and nonhuman) of care networks (social workers, durable medical providers, doctors, hospitals, family members, government programs, government surveillance mechanisms, qualifying criteria, and many more).…”
Section: Discussionmentioning
confidence: 99%
“…My research has identified the need for more attention to the materiality of family caregiving of children needing long‐term care in feminist geography literature. Feminist techno‐scientists and posthumanists are questioning human/nonhuman relations and theorizing about mother/child assemblages that recenter discourses away from medical and social models of disability (Goodley et al., 2014; Hamraie, 2015; Haraway, 2013; Jampel and Bebbington, 2018). This work contributes to that discussion by not only presenting Jane and Ichabod as individuals but also as assemblages that function (or not) within wider power assemblages (human and nonhuman) of care networks (social workers, durable medical providers, doctors, hospitals, family members, government programs, government surveillance mechanisms, qualifying criteria, and many more).…”
Section: Discussionmentioning
confidence: 99%